Calibration and Cross-validation of Accelerometry in Children and Adolescents with Cystic Fibrosis. Issue 1 (2nd January 2023) - Bianchim, Mayara S.; McNarry, Melitta A.; Evans, Rachel; Thia, Lena; Barker, Alan R.; Williams, Craig A.; Denford, Sarah; Mackintosh, Kelly A
ABSTRACT: Commonly used cut-points may misclassify physical activity (PA) in people with cystic fibrosis (CF). The aim of this study was to develop and cross-validate condition-specific cut-points in children and adolescents with CF. Thirty-five children and adolescents with CF (15 girls; 11.6 ± 2.8 years) and 28 controls (16 girls; 12.2 ± 2.7 years), had their energy expenditure and triaxial acceleration measured during six daily activities of varying intensities. Euclidean Norm Minus One (ENMO) and Mean Amplitude Deviation (MAD) were extracted using both GENEActiv (both wrists) and ActiGraph GT9X (both wrists and right waist) accelerometers. ROC curves were used to determine healthy and CF-specific raw acceleration cut-points for sedentary time (SED), moderate physical activity (MPA) and vigorous physical activity (VPA). The PA cut-points were generally lower in CF compared to controls for both ENMO (60.2–73.1 vs. 63.5–86.8 mg) and MAD (58.9–85.2 vs. 75.9–93.7 mg). These substantial inter-cut-point differences support the need for disease-specific cut-points.